ANALISIS PENGARUH SPIRITUALITAS DI TEMPAT KERJA TERHADAP KEPUASAN KERJA KARYAWAN DENGAN KEPERCAYAAN KARYAWAN SEBAGAI VARIABEL INTERVENING - Adetya, Intan Vini; Andriyani, Andriyani (Diponegoro Journal of Management, 2024)
ABSTRACT Employee job satisfaction is a critical factor affecting employee decisions to stay within an organization. This phenomenon is not an exception in the context of hospitals. The challenging work conditions in hospitals can lead to indications of job dissatisfaction among both medical and non-medical staffs, ultimately increasing the chance of employees leaving their job. Prior research has indicated that job satisfaction is not only derived from the fulfillment of material needs but also from spiritual well-being. This study explores the impact of workplace spirituality on job satisfaction and the analysis of the mediating effect of employee trust. The research sample was selected using purposive sampling method, involving employees from Rumah Sakit Advent Medan. A total of 179 medical and non-medical staffs who had superiors were included as respondents in this study. The data from the respondents were analyzed using Structural Equation Modeling (SEM) with second-order/higher-order constructs, utilizing SmartPLS 3.2.9 for Mac. The findings reveal that workplace spirituality has a positive and significant impact on employee job satisfaction and employee trust. Similarly, the influence of employee trust on job satisfaction was found to be significantly positive. It was also found that employee trust partially mediated the indirect influence of workplace spirituality on job satisfaction.